Emotional Literacy in Learning to Write Descriptive Texts Through The Multisensory PjBL Model Based on Favorite Objects in Elementary Schools - Encil Puspitoningrum; Yuni Pratiwi; Titik Harsiati (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This research examines the effectiveness of a multisensory Project-Based Learning (PjBL) model based on cherished objects in enhancing the emotional literacy of fourth-grade elementary school students when writing descriptive texts. Using a descriptive phenomenological qualitative approach, the study involved 28 students from SD Muhammadiyah 9 Malang in the 2025/2026 academic year. Data were collected through participant observation (8 meetings), in-depth interviews, text analysis and reflection journals. The results show a significant improvement in the quality of the descriptive texts (average +64.6%), particularly in the expression of personal emotions (+110.7%) and sensory vocabulary (+72.0%). Four main themes emerged: high emotional engagement, enrichment of sensory-affective details, development of self-awareness and self-regulation, and the transfer of emotional literacy to daily life (86.7% of parents reported their children being more open). The model successfully transformed student writing from mechanical prose into authentic and expressive narratives. The multisensory PjBL model based on cherished objects proved effective in integrating the affective dimension into descriptive text writing instruction and aligns with the holistic spirit of the Merdeka Curriculum.